2003
DOI: 10.1554/0014-3820(2003)057[0883:gboafm]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Benefits of a Female Mating Preference in Gray Tree Frogs Are Context-Dependent

Abstract: Good genes'' models of sexual selection predict that male courtship displays can advertise genetic quality and that, by mating with males with extreme displays, females can obtain genetic benefits for their offspring. However, because the relative performance of different genotypes can vary across environments, these genetic benefits may depend on the environmental context; in which case, static mating preferences may not be adaptive. To better understand how selection acts on the preference that female gray t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 86 publications
3
68
0
Order By: Relevance
“…Plasticity in female mating preferences is favored by the confluence of environmental patchiness and variation in an assessable male trait under habitat-imposed viability selection (see Alonzo and Sinervo 2001;Doty and Welch 2001;Welch 2003). Migration between habitats further relaxes the conditions that favor plastic phenotypes (Sultan and Spencer 2002).…”
Section: Selection In the Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasticity in female mating preferences is favored by the confluence of environmental patchiness and variation in an assessable male trait under habitat-imposed viability selection (see Alonzo and Sinervo 2001;Doty and Welch 2001;Welch 2003). Migration between habitats further relaxes the conditions that favor plastic phenotypes (Sultan and Spencer 2002).…”
Section: Selection In the Fieldmentioning
confidence: 99%
“…With temporal or spatial variation in genotype quality, plastic mate preferences may be favored over static mate preferences (Lesna and Sabelis 1999; Doty and Welch 2001;Welch 2003). Context-dependent female choice for good genes could then promote adaptive response to prevailing ecological conditions without eroding variation in the male traits on which preferences are based (Jia et al 2000;Labeyrie et al 2003).…”
mentioning
confidence: 99%
“…However, it is now recognized that benefits from mate choice can depend on the genetic match between males and females or the ecological and social context (e.g., Qvarnström 2001;Welch 2003;Suk and Choe 2008). Recently, Chaine and Lyon (2008) showed that individual female lark buntings (Calamospiza melanocorys) change their preferences for particular male traits between years.…”
Section: Discussionmentioning
confidence: 99%
“…This is 501 comparatively easily achieved in laboratory studies of externally fertilising species by means of 502 split-clutch in-vitro fertilisations (e.g. Barber et al 2001;Welch 2003) and feasible to some 503 degree within captive (semi-natural) populations of certain internally fertilising species (e.g. 504…”
Section: Context-dependent Genetic Effects Of Extra-pair Mating 275mentioning
confidence: 99%